2008
DOI: 10.1007/s11746-008-1256-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Conventional and High‐Oleic Vegetable Oils with Added Antioxidants

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
2
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 23 publications
(23 reference statements)
7
51
2
9
Order By: Relevance
“…Many authors have previously shown that vegetable oils with the highest OA content were the most resistant to autoxidation (with or without added oxidants) [38][39][40]. Kerrihard et al [37] justified the magnitude of fat oxidation with the corresponding composition and proportions of monounsaturated, diunsaturated and triunsaturated FA (MUFA:DiUFA: TriUFA) in foods.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…Many authors have previously shown that vegetable oils with the highest OA content were the most resistant to autoxidation (with or without added oxidants) [38][39][40]. Kerrihard et al [37] justified the magnitude of fat oxidation with the corresponding composition and proportions of monounsaturated, diunsaturated and triunsaturated FA (MUFA:DiUFA: TriUFA) in foods.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…Thus, an increase in oxidative stability is comparable to the results obtained in the studies employing different 00-rapeseed varieties as a research material, which is subjected to roasting prior to pressing (Prior et al, 1991b;Górecka et al, 2003;Wijesundera et al, 2008). An increased oleic acid content and decreased α-linolenic acid content in high-oleic rapeseed oil is believed to play the main role in increasing the oxidative stability of oils (Merrill et al, 2008). The effects of roasting conditions on the oxidative stability of the oil obtained from higholeic rapeseed have not yet been investigated.…”
Section: Effect Of Roasting Conditions On the Oil Stabilitymentioning
confidence: 99%
“…The physical and chemical properties of vegetable oils can be modified through the genetic modification of oilseeds such as canola, soybean, corn and sunflower. Modifying the fatty acid composition by decreasing the amount of oxidizable fatty acids such as α-linolenic and linoleic acids and increasing the amount of oxidation-resistant fatty acids such as oleic acid improved the oil's oxidative stability (Merrill et al, 2008). Such enhancement of a genetically diverse gene pools is an essential plant breeding requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Os óleos vegetais em geral são sensíveis a diversos fatores capazes de alterar suas qualidades. Dentre estes, tem-se a degradação imposta pelo ar ambiente ou autoxidação; pela termo-oxidação e a imposta pela luz ou fotoxidação, forma de degradação importante na presença de um fotossensibilizador com adição de oxigênio aos ácidos graxos insaturados; essa adição reage com as insaturações convertendo o oxigênio em sua forma mais reativa (SMOUSE, 1995;COPPIN;PIKE, 2001;MERRILL et al, 2008).…”
Section: Evaluation Of Thermal-oxidative Behavior and Spectroscopic Punclassified
“…As modificações bioquímicas podem ser relacionadas a aspectos como a umidade, a atividade enzimática e a presença de microorganismos. As outras alterações como as químicas, destacadas anteriormente, são a autoxidação e a fotoxidação, que ocorrem nesses materiais com a interação do oxigênio, pelo grau de insaturação nos ácidos graxos, na presença da luz, de temperatura e na presença de antioxidantes e de pró-oxidantes, dentre outros aspectos (SMOUSE, 1995;DUNN, 2005;MERRILL et al, 2008;FONSECA, 2009 (SMOUSE, 1995;JADHAV et al, 1996;RUDNIK et al, 2001). …”
Section: Evaluation Of Thermal-oxidative Behavior and Spectroscopic Punclassified